Enhancement of the Cancellation-and-Focus Model : a consumer's perspective. - Ho, Stella Hwee Mein. (2008)
Our study proposes that there is an inaccuracy in the cancellation-and-focus model (Houston, D.A. Sherman, S.J., 1995): shared features are not automatically cancelled out because they are common. The relevancy of the shared features will determine if they are ignored in the decision-making process.